1998
DOI: 10.1136/bmj.316.7144.1588
|View full text |Cite
|
Sign up to set email alerts
|

Children and the inverse care law

Abstract: It is over 25 years since Tudor Hart described the inverse care law. This states that "the availability of good medical care tends to vary inversely with the need for it in the population served."1 Although Tudor Hart did not provide hard evidence to support his hypothesis, others have since. West and Lowe showed that for children's services need and provision were badly matched.2 Given the lack of strategic planning centred on children and the low priority given to the commissioning of children's services, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
24
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 11 publications
3
24
0
Order By: Relevance
“…Children in refuges for women victims of domestic violence constitute one of several marginalised groups with poor access to services 1. They are a largely unstudied population, although a pilot study in Wales identified poor uptake of immunisation and surveillance 2.…”
Section: Introductionmentioning
confidence: 99%
“…Children in refuges for women victims of domestic violence constitute one of several marginalised groups with poor access to services 1. They are a largely unstudied population, although a pilot study in Wales identified poor uptake of immunisation and surveillance 2.…”
Section: Introductionmentioning
confidence: 99%
“…As a group, LAYP looked after young people have multiple disadvantages and may have experienced abuse, neglect and family breakdown before entering care, and being subject to decisions out of their control. This, which all contributes to their distrust of, and lack of, engagement with health promoting services (Webb, 1998). As a consequence, supporting behaviour change in looked after young people LAYP is more challenging.…”
Section: Introductionmentioning
confidence: 99%
“…All children from marginalised populations face this double jeopardy. For many, such as travellers, homeless families, children living rough, and asylum seeking and refugee children,3 this is because of poor access to both mainstream and specialist services 4. For others, ironically, it is because a specific health or social care need has been identified and led to the provision of selective services.…”
mentioning
confidence: 99%